PENGARUH PENYAJIAN LAPORAN KEUANGAN AKSESIBILITAS LAPORAN KEUANGAN DAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH (Studi Empiris Pada OPD Pemerintah Kabupaten Indragiri Hulu) - Nuria Rahma; Restu Agusti; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effect of presentation of financial statements accessibility of financial statements and internal control system of government on accountability of financial management. The sampling in this study were which consists of Head OPD, Head of Finance OPD, and Treasurer Expenditure OPD Indragiri Hulu regency government. The sampling technique used purposive sampling method. Data of this study uses primary data directly through a questionnaire and analyzed using SPSS 21. Technical analysis of the data to test the hypothesis using multiple linear regression analysis approach. Based on the results of the study stated that the presentation of financial statements, accessibility of financial statements and internal control systems of government affect the accountability of financial management. Contributions the influence of financial statement presentation, accessibility of financial report and internal control system of government explain accountability of local financial management in OPD of Indragiri Hulu Regency equal to 83,6%. While the remaining 16.4% influenced by variables not observed in this study.Keywords : presentation of financial statements, accessibility of financial statements, internal control system of government, and accountability.